Psychometrics and diagnostic properties of the Montreal Cognitive Assessment 5‐min protocol in screening for Mild Cognitive Impairment and dementia among older adults in Tanzania: A validation study. (13th September 2020) - Masika, Golden M.; Yu, Doris S. F.; Li, Polly W. C.; Wong, Adrian; Lin, Rose S. Y.
Abstract: Background: The prevalence of dementia in Tanzania, as in other developing countries, is progressively increasing. Yet international screening instruments for mild cognitive impairment are lacking. Objectives: The aim of this study was to determine the psychometrics and the diagnostic ability of the Montreal Cognitive Assessment 5 minutes protocol (MoCA‐5‐min) among older adults in the rural Tanzania. Methods: The MoCA‐5‐min and the Identification and Intervention for Dementia in Elderly Africans (IDEA) cognitive screening were concurrently administered through face to face to 202 community‐dwelling older adults in Chamwino district. Exploratory factor analysis (EFA) using principal component method and oblique rotation was performed to determine the underlying factor structure of the scale. The concurrent and construct as well as predictive validities of the MoCA‐5‐min were examined by comparing its score with IDEA cognitive screening and psychiatrist's diagnosis using DSM‐V criteria, respectively. Results: The EFA found that all the MoCA‐5‐min items highly loaded into one component, with factor loading ranging from 0.550 to 0.879. The intraclass correlation coefficient for 6 weeks test‐retest reliability was 0.85. Its strong significant correlation with the IDEA screening (Pearson's r = 0.614, p < 0.001) demonstrated a good concurrent validity. Using the psychiatrist's rating as the gold standard, MoCA‐5‐min demonstrated the optimal cut‐off score for MCI at 22, which yielded the sensitivity of 80% and specificity of 74%; and dementia at score of 16 giving a sensitivity of 90% and specificity of 80%. Upon stratifying the sample into different age groups, the optimal cut‐off scores tended to decrease with the increase in age. Conclusion: The MoCA‐5‐min is reliable and provides a valid and accurate measure of cognitive decline among older population in the rural settings of Tanzania. The use of varying cut‐off scores across age groups may ensure more precise discriminatory power of the MoCA‐5‐min. Implications for practice: Availability of the MoCA‐5‐min in Tanzania will facilitate clinicians to timely detect dementia at both pre‐clinical and clinical stages. Its availability will also encourage further research and international collaborations in dementia prevention programs.